Pólen de Melipona fasciculata Smith: valor nutricional e atividades biológicas - MESQUITA, José Wilson Carvalho de (2021)
Research into bioactive ingredients for human use has increased as result of greater consumer awareness of the relationship between these products and associated benefits related to health and well-being. Bee products such as honey, propolis, geopropolis, wax, royal jelly and pollen have been used since antiquity for their therapeutic properties and nutraceutical potential. Considering the production chain, bioactivity and chemical composition of Melipona fasciculata products this study proposed the palynological characterization, physicochemical, chemical, nutritional profile, antioxidant and anti-inflammatory properties of M. fasciculata pollen extracts cultivated in Maranhão. A total of 17 pollen samples of M. fasciculata were collected between April 2015 and April 2017 in 5 municipalities in the state of Maranhão, covering the biomes with the largest area in the state in some of their phytogeographic profiles. The palynological analysis of the collected samples showed the dominant pollen types in Santa Luzia do Paruá as Borreria verticillata (Rubiaceae), Hyptis sp. (Lamiaceae), Protium sp. (Burseraceae), Senna sp. (Fabaceae) and Mauritia sp. (Arecaceae), Palmeirândia, Viana and Anajatuba were Pontederia parviflora (Pontederiaceae) and Myrcia sp. (Myrtaceae) and those of Chapadinha, Mimosa sp. (Mimosaceae) and Eucalyptus sp. (Myrtaceae). The microbiological analysis showed all the samples with very low presence of microbiological contaminants. The nutritional composition indicated that the samples presented similarity and that they are within the parameters recommended by the Ministry of Agriculture, except for humidity for two samples and ash content for one. The samples were grouped according to their locality of collection and climatic seasonality (dry season and rainy season), after which they were extracted by maceration for 72 hours with 70% ethanol and 1: 8 hydromodule, totalizing 10 pollen extracts. The extraction yield varied between 53.8 and 64.8%. The extracts obtained were submitted to the total flavonoid and total phenolic compounds assays. The extracts of pollen from Santa Luzia do Paruá (rainy season), Palmeirândia (dry season), Viana (dry season), Anajatuba (rainy season) and Chapadinha (dry season) were submitted to high efficiency liquid chromatography with UV detector -Vis. The presence of β-sitosterol, ellagic acid, coumaric acid, isoquercitrin, quercitrin, myricetin, naringenin, canferol, catechin, β-amirine, coumaric acid, rutin, quercetin, gallic acid and apigenin. The extracts obtained from the pollen samples of M. fasciculata collected in Santa Luzia do Paruá (ESLPs and ESLPc), Palmeirândia (EPALs and EPALc) and Chapadinha (ECHAs) were fractionated and each of their fractions was submitted to the evaluation of the antioxidant activity by the DPPH assay. The result of the evaluation of the antioxidant activity expressed in EC50 varied between 156.24 and 1764.67 μg/ml. The chloroform fractions of all the samples presented better antioxidant activity. The extracts obtained from pollen samples of M. fasciculata collected in Santa Luzia do Paruá in the rainy season (ESLPc), Palmeirândia in the rainy season (EPALc) and Chapadinha in the dry season (ECHAs) were used to evaluate the anti-inflammatory activity in vitro by the inhibition test of cyclooxygenases 1 and 2. The Chapadinha sample presented the highest percentages of enzymatic inhibition in the concentrations of 10 and 50 μg/mL, reaching to inhibit 61.7 and 58.6% of COX1 and COX2, respectively.